THE HINLOPEN SLIDE: A GIANT, SUBMARINE SLOPE FAILURE ON THE NORTHERN SVALBARD MARGIN, ARCTIC OCEAN - Vanneste M.; Mienert J.; Bünz S. (My University, 2006)
New swath bathymetry data unveil a giant, submarine landslide located at the mouth of the Hinlopen transverse trough on the northern Svalbard margin, Arctic Ocean. Despite the relatively small drainage and slide scar areas, the Hinlopen Slide is exceptional in volume, headwall height and dimensions of the rafted blocks. From the c. 2200 km2 large headwall area, approximately 1350 km3 of Plio-Pleistocene sediments have been evacuated from the continental margin to the Nansen Basin. The escarpment heights are unprecedented, exceeding 1400 m, whereas the rafted blocks observed in the intermediate part of the slide area are up to 450 m high and more than 5 km wide. These characteristics make the Hinlopen Slide one of the largest landslides worldwide, and the first mapped mega-slide in the Arctic Ocean. Within the amphitheatre-shaped slide scar area, a composite set of escarpments and multiple, roughly planar slip surfaces occur, as well as detached sediment ridges adjacent to the outer escarpment, arcuate pressure ridges in debris lobes and isolated slump debris or blocks. From this complex slide scar geomorphology, we infer that the Hinlopen Slide was a translational, multi-phase slope failure that developed retrogressively. The slide has not been dated yet; however, the geophysical data suggest a relatively young age, though probably pre-Holocene, inferred from the pattern of sediment infill within the slide scar area derived from the Hinlopen cross-shelf trough. A submarine landslide with these dimensions could have created a devastating tsunami, although its potential depends on sea ice conditions as well as the time lags of the multi-phase, retrogressive movement. Climate changes and the response of ice sheets, ocean-current systems, sediment delivery and seismicity related to glacio-isostatic deformation appear as critical factors controlling stability on glaciated margins. © 2006 Elsevier B.V. All rights reserved.
Keywords: ARCTIC OCEAN; GLACIATED MARGIN; HEADWALL; HIGH-LATITUDE SUBMARINE SLOPE FAILURE; HINLOPEN; NORTHERN SVALBARD MARGIN; RAFTED BLOCKS; SWATH BATHYMETRY; Holocene; Pleistocene; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен; Cenozoic::Quaternary::Pleistocene; Кайнозой::Четвертичная::Плейстоцен